Effectiveness of security controls on electronic health records - Wanyonyi, Everleen; Rodrigues, Anthony; Abeka, Silvance O.; Ogara, Solomon (IJSTR, 2017)
Electronic Health Record (EHR) systems enhance efficiency and effectiveness in handling patients ‘information in healthcare. This study focused on the EHR security by initially establishing the nature of threats affecting the system and reviewing the implemented security safeguards. The study was done at a referral hospital (level 6) government facility in Kenya. Purposive sampling was used to select a sample of 196 out of 385 staff and a questionnaire designed for qualitative data collection. Data was analyzed using SPSS software. Correlations and binary logistic regression were obtained. Binary Logistic Regression (BLR) was used to establish the effect of the safeguards (predictors) on EHR security. It was established that physical security contributes more to the security of an information system than administrative controls and technical controls in that order. BLR helped in predicting effective safeguards to control EHR security threats in limited resourced public health facilities.
Keywords: electronic health records; cyber security; safeguards; binary logit function